1994
DOI: 10.2307/3869982
|View full text |Cite
|
Sign up to set email alerts
|

Two Classes of Homeodomain Proteins Specify the Multiple A Mating Types of the Mushroom Coprinus cinereus

Abstract: The A mating type locus of the mushroom Coprinus cinereus regulates essential steps in sexual development. The locus is complex and contains several functionally redundant, multiallelic genes that encode putative transcription factors. Here, we compare four genes from an A locus designated A42. Overall, the DNA sequences are very different (approximately 50% homology), but two classes of genes can be distinguished on the basis of a conserved homeodomain motif in their predicted proteins (HD1 and HD2). Developm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

1998
1998
2008
2008

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 26 publications
2
21
0
Order By: Relevance
“…It is not known whether the A mating-type products are positive or negative regulators of development, since morphological observations do not show whether a regulatory effect is direct or indirect. Analysis of monokaryons transformed with A genes of another specificity ("A on" transformants) revealed a negative function of compatible A genes on the production of oidia and positive effects not only on the formation of clamp cells but also on the formation of chlamydospores, hyphal knots, and fruiting-body initials (232,258,261,307,358,477), consistent with the earlier observations with common B heterokaryons and Amut homokaryons (see above) ( Table 1). The mating-type-encoded transcription factors of C. cinereus and other basidiomycetes (S. commune and Ustilago spp.)…”
Section: Mating-type Locisupporting
confidence: 79%
See 3 more Smart Citations
“…It is not known whether the A mating-type products are positive or negative regulators of development, since morphological observations do not show whether a regulatory effect is direct or indirect. Analysis of monokaryons transformed with A genes of another specificity ("A on" transformants) revealed a negative function of compatible A genes on the production of oidia and positive effects not only on the formation of clamp cells but also on the formation of chlamydospores, hyphal knots, and fruiting-body initials (232,258,261,307,358,477), consistent with the earlier observations with common B heterokaryons and Amut homokaryons (see above) ( Table 1). The mating-type-encoded transcription factors of C. cinereus and other basidiomycetes (S. commune and Ustilago spp.)…”
Section: Mating-type Locisupporting
confidence: 79%
“…Other, nondiscriminating dimerization domains were predicted to localize directly C-terminal to the HD1 homeodomains (131,254). Remarkably, there is a significant identity between a short sequence downstream of the homeodomain in HD1 proteins to the 20-aa C-terminal tail of the homologous matingtype protein ␣2 of S. cerevisiae (172,258) (Fig. 14).…”
Section: Vol 64 2000 Developmental Processes In Coprinus Cinereusmentioning
confidence: 98%
See 2 more Smart Citations
“…Next to eliciting typical features of the dikaryotic mycelium (e.g. clamps cells and clamp cell fusion; Kües et al 1992, 1994a,c, Badalyan et al 2004), the A mating type genes were shown to induce hyphal knot and primordia development ) and the B mating type genes to support the A mating type genes in initiation of fruiting body development and to act in fruiting body maturation at the stage of karyogamy (Kües et al 2002b). Therefore not surprisingly, certain mutations in the mating type loci (Kües et al 1994b, Pardo et al 1996, Olesnicky et al 1999, Srivilai et al 2006b) make fruiting body development independent from dikaryon formation (Swamy et al 1984).…”
Section: Genetic Access Of Fruiting Body Developmentmentioning
confidence: 99%